KNOWLEDGE RELATIONSHIP WITH THE STATUS OF DENTAL AND ORAL HYGIENE OF ORTHODONTIC USERS IN STUDENTS INTEGRATED CAMPUS OF POLTEKKES ACEH MINISTRY OF HEALTH. - Cut Aja Nuraskin; Julia Maulana (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
Orthodontic treatment is a treatment to correct malocclusion and restore structural and esthetic function. The purpose of this study was to analyze the relationship between knowledge of maintaining oral and dental hygiene of orthodontic users with dental hygiene status in Poltekkes Kemenkes Aceh students. The research method is analysis with a cross-sectional research design with a purposive sampling technique, carried out from April 1 to April 22, 2021, with 40 respondents using orthodontic students from the Health Polytechnic of Aceh. The results of the study were statistically significant with the Spearman correlation test between knowledge and OHI-S (p=0.039). The results of the study were based on the knowledge of 23 people (57.5%) with good knowledge, and 17 people (42.5%) with less knowledge. The results of the OHI-S study were 6 people (15.0%) good, 15 people (37.5%) moderate OHI-S, and 19 people (47.5%) bad OHI-S. The conclusion is that there is a relationship between knowledge of maintaining oral and dental hygiene by orthodontic users with dental hygiene status in Poltekkes Kemenkes Aceh students.